Hidrogéis de galactomanana e de blendas de galactomanana/amido como veículo para liberação controlada da astaxantina - Pereira, Vanessa de Abreu (2016)
The seeds of the species Prosopis juliflora (mesquite) are a potential source of galactomannan (GM). The crosslinking formation among the polymer chains allows to obtaining hydrogels with good mechanical stability, but with low resistance in water. The preparation of polymer blends of galactomannan / starch (GM / ST) is an alternative to reduce this hydrophilicity, therefore, which makes it attractive for incorporation of bioactive compounds such as astaxanthin (AST), unstable carotenoid. In addition to protecting the compound, hydrogels formed by the blend have a duty permit a controlled release. The objective of this work was to produce and characterize hydrogels of galactomannan (HGM) and hydrogels of blend of galactomannan / starch (HGMAM) as a vehicle for controlled release of AST. Thus, it has been proposed to obtain AST from supercritical fluid extraction (FSC) of salmon`s residue. HGM were prepared varying the concentration of this biopolymer and HGMAM using borax as a crosslinker. Furthermore, emulsions were produced containing the extract obtained from salmon and AST in the form of a supplement (capsule) to be used as a means of synthesis of hydrogels. The extracts were characterized according to AST content by spectrophotometry to its antioxidant activity (AA), fatty acid composition and spectroscopy in the infrared (FTIR). Furthermore, hydrogels were characterized by humidity, gel strength (GS), FTIR, thermal gravimetric analysis (TGA) and in vitro release of astaxanthin. The higher content obtained was AST 1268 mg / 100 g of salmon extract obtained using 300 bar and 50° C, while a higher AA 91.47% and an increased content of unsaturated fatty acids 83.40% were found under a condition of 200 bar and 60 °C. A higher SG 0.474 N was obtained for the hydrogel with higher concentration of GM, and in relation the AST, a higher SG 0,084N was obtained to hydrogel with a higher concentration of salmon extract containing a lower concentration of this carotenoid. The thermograms revealed a mass loss for HGM around 28.4% to 348.5 ° C, related to the polymer decomposition, whereas for GM was obtained value of mass lost of 64.17% to 306.75° C. The humidity for HGM ranged between 92.58 and 98.79%. In the FTIR spectrum for the hydrogel was observed the absence of a band at 869 cm-1, characteristic of anomeric linkages of the mannose units present in GM. As for the extracts and the hydrogels containing the extract were obtained bands attributed to the isoprenoid chain AST. The hydrogel containing the salmon extract showed maximum released of 96% of astaxanthin after 50 minutes, while that obtained with the capsule was 80.5%. Based on the results, was observed the effect of extraction conditions to determine the AST level in AA and composition of fatty acids in the extracts. Furthermore, it was found that cross-linking and the concentration of AST increased the thermal stability of HGM that the concentration of GM and the reduction of the concentration of AST caused greater FG and a lower humidity. It is possible to verify the occurrence of crosslinks among chains of mannose and borax ions from FTIR spectra, in addition to the characteristic bands of isoprenoid chain in AST. The results also revealed the influence of the active ingredient composition on the kinetics of release of AST, where the use of the blend GM / ST in forming the hydrogel proved to be a viable alternative to the release of the carotenoid, targeting an application as a nutritional supplement.